Flouting Maxim Analysis in Bill Gate's Utterances on Ellen Talk Show (Pragmatic Approach) - Silvia Nanda Putri Erito (Universitas Musamus, 2021)
Abstract In communication, people usually apply the cooperative principle that consists of four maxims of conversational maxims for several reasons in several contexts. Speakers obey these maxims to have effective communication without any miscommunication. Flouting the maxims is a situation wherein the speakers cause misunderstanding on their participants’ part or to achieve some other purposes in conversation. The objective of this study intends to analyze the types of maxims that flout by Bill gates’ utterances. The data were collected by using video observation. The video is taken from the youtube channel The Ellen Show. The data analysis was done by (1) eliciting the video from youtube channel, (2) observing the data by watching and listening to the talk show, (3) transcribing the script, (4) analyzing the types of maxims that flout by Bill gates, (5) categorizing the data, (6) Finding the data (7) concluding the study. The finding shows a maxim of quantity is the most floating by Bill gates.